2023
DOI: 10.3390/plants12112113
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Post-Translational Regulation of Plant bHLH Transcription Factors during the Response to Environmental Stresses

Abstract: Over the past decades, extensive research has been conducted to identify and characterize various plant transcription factors involved in abiotic stress responses. Therefore, numerous efforts have been made to improve plant stress tolerance by engineering these transcription factor genes. The plant basic Helix–Loop–Helix (bHLH) transcription factor family represents one of the most prominent gene families and contains a bHLH motif that is highly conserved in eukaryotic organisms. By binding to specific positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 151 publications
0
3
0
Order By: Relevance
“…In turn, Radani et al [12] focus in their article on the Helix-Loop-Helix (bHLH) plant family TFs, involved in responses to abiotic stress, representing one of the most important families of eukaryotic genes containing the highly conserved bHLH motif. These factors activate or repress the transcription of specific response genes and thus influence the response to abiotic stresses such as drought, climate change, mineral deficiencies, excessive salinity, and water stress, and the regulation of these factors is crucial in achieving a better control of their activity.…”
Section: Variamentioning
confidence: 99%
“…In turn, Radani et al [12] focus in their article on the Helix-Loop-Helix (bHLH) plant family TFs, involved in responses to abiotic stress, representing one of the most important families of eukaryotic genes containing the highly conserved bHLH motif. These factors activate or repress the transcription of specific response genes and thus influence the response to abiotic stresses such as drought, climate change, mineral deficiencies, excessive salinity, and water stress, and the regulation of these factors is crucial in achieving a better control of their activity.…”
Section: Variamentioning
confidence: 99%
“…Due to their regulatory effects on many genes involved in adverse conditions, TFs are generally considered one of the most appropriate genetic targets for the molecular breeding and development of stress-tolerant crop varieties, e.g., inducing drought response in plants [12,13]. Studies have shown that a large number of TFs, e.g., NAC [14], AP2/ERF [15], bZIP [16], bHLH [17], MYB [18,19], and WRKY [20], are frequently involved in the plant response to water stress. In particular, NAC TFs are one of the largest families of plant-specific transcriptional regulators and are widely distributed in plants, including mosses, ferns, gymnosperms, and angiosperms [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…A pivotal role in this process is played by cis-active elements localized in the gene promoter region, which are bound by particular transcription factors [17]. The activation of trans-factors, being a prerequisite to DNA-binding and gene expression regulation, is facilitated by numerous signaling routes, which adjust the gene expression level to the particular needs of cells [18,19]. External signals are delivered by activated gene-specific trans-factors to the multisubunit Mediator complex, interacting with general trans-factors complexed with RNA polymerase II [20].…”
Section: Introductionmentioning
confidence: 99%